Lymph Node Metastases and Prognosis in Penile Cancer - Zhu, Yao; Ye, Ding-wei (Chinese Journal of Cancer Research; Vol 24, No 2 (June 29, 2012): Chinese of Journal Cancer Research, 2012)
Lymph node status is a key prognostic factor in penile squamous cell carcinoma. Recently, growing evidence indicates a multimodality approach consisting of neoadjuvant chemotherapy followed by consolidation surgery improves the outcome of locally advanced penile cancer. Thus, accurate estimation of survival probability in node-positive penile cancer is critical for treatment decision making, counseling of patients and follow-up scheduling. This article reviewed evolving developments in assessing the risk for cancer progression based on lymph node related variables, such as the number of metastatic lymph nodes, bilateral lymph node metastases, the ratio of positive lymph nodes, extracapsular extension of metastatic lymph nodes, pelvic lymph node metastases, metastatic deposit in sentinel lymph nodes and N stage in TNM classification. Controversial issues surrounding the prognostic value of these nodal related predictors were also discussed.